THE EFFECT OF FINANCIAL LITERACY ON CHILDREN’S FINANCIAL MANAGEMENT AT THE AT-TANZIL LEARNING CENTER, MALAYSIA - Luthfi Ayu Ananda; Sri Rahayu; Muhammad Arif Rakhman (Jurnal Interprof, 2026)
Purpose: This study aims to examine the effect of financial literacy on childern’s financial management at the At-Tanzil learning Center, Malaysia. Research Methodology: This study adopted a quantitative research approach using a survey method. Data were collected from all 50 children who met the research criteria through a saturated sampling technique. The research instrument consisted of a structured questionnaire developed from the indicators of each variable and measured using a five-point Likert scale. The collected data were analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) approach with the support of SmartPLS software. Results: The findings show that financial literacy has a positive and significant effect on financial management variable has an R-squared value of 0.865 and an adjusted R-squared value of 0.856. These results indicate that Financial Knowledge, Financial Skills, and Financial Behavior collectively account for 86.5% of the variation in Children’s Financial Management.   Conclusions: Financial literacy education should be provided on an ongoing basis starting at an early age so that children not only understand theoretical financial concepts but are also able to apply them in their daily lives. Children are expected to develop good, wise, and responsible financial habits from an early age. Limitations: This study is limited to children at the At-Tanzil Learning Centre in Malaysia and examines only their financial knowledge in relation to financial management. Contributions: This study expands the research on financial literacy among children by breaking down financial literacy into three main dimensions financial knowledge, financial skills, and financial behavior and then examining the influence of each dimension on children’s financial management. This approach provides a more comprehensive understanding of the components of financial literacy that play the most significant role xplain how this study can contribute in developing financial management skills from an early age.